Parishin B blocking TRIB3-AKT1 interaction inhibits breast cancer lung metastasis - Cheng, Xiongtao; Sun, Jianguo; Chen, Shouhong; Wang, Nan; Tang, Weijing; Xia, Zijian; Shu, Yuhong; Gao, Shouhong; Wang, Zhipeng; Wang, Xinxia; Shao, Rongzi; Cao, Jianxiong (Frontiers in Pharmacology, 2025)
BackgroundTRIB3 has been reported to mediate breast cancer (BC) proliferation and metastasis by interacting with AKT1, and blocking the interaction between TRIB3 and AKT1 can inhibit the progression of BC. Besides, inhibiting TRIB3 to turn “cold tumor” hot has also been proved to be an effective therapeutic strategy for BC. Thus, this study aim to find drugs that can bind to TRIB3 to inhibit BC progression, and further elucidate its mechanism.MethodsThe possible inhibitors of TRIB3 were screened by high-throughput molecular docking, CETSA, and CO-IP assay. Then, the effect of TRIB3 inhibitor anti BC was assessed by CCK-8 assay, flow cytometry, plate colony formation assay, and transwell assay; and the RNA-seq was empolyed to study the potential mechanism of Parishin B (PB) anti-BC. Finally, the effect of TRIB3 inhibitor on BC lung metastasis in vivo was evaluated.ResultsPB was screened as a possible inhibitor of TRIB3, and CETSA and CO-IP assay indicated that PB could target TRIB3 and block TRIB3-AKT1 interaction. In addition, PB exhibited good anti-BC activity without drug toxicity in normal breast cells by experiments in vitro, and RNA-seq analysis suggested PB could inhibit the proliferation and invasion of BC cells related with cell cycle. It was also proved that PB could inhibit BC lung metastasis in vivo.ConclusionThe study demonstrated PB can bind to TRIB3 to inhibit BC proliferation and lung metastasis by blocking TRIB3-AKT1 interaction and regulating cell cycle, providing a therapeutic agent for the treatment of BC.